Switchable surfactants at the polystyrene–water interface: effect of molecular structure. Issue 2 (1st June 2014) - Su, Xin; Jessop, Philip G.; Cunningham, Michael F.
Abstract : Polystyrene (PS) latexes prepared with either C12 N (N'-dodecyl-N, N-dimethylacetamidinium bicarbonate) or C12 E2 N (N'-(2-(2-(dodecyloxy)ethoxy)ethyl)-N, N-dimethylacetamidinium bicarbonate) switchable surfactants are stable when CO2 is present, aggregate when CO2 is removed and can be redispersed by readdition of CO2 . The surface coverage of the latex with surfactant drops significantly when CO2 is removed. For PS latexes with C12 N, the surface coverage does not return to the original value when CO2 is reintroduced, but the coverage of the latex with C12 E2 N does return to the initial value. The redispersion process of the PS latex with C12 E2 N occurs much more rapidly when sparging with CO2 . Both C12 N and C12 E2 N behave as surfactants in the presence of CO2, but in the absence of CO2, only C12 E2 N continues to have some surface activity. Due to their different molecular structures, their solid surface adsorption behaviors differ. With or without CO2, C12 E2 N exhibits monolayer adsorption on the surface of the latex particle.